2016
DOI: 10.7150/jca.14790
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of Tubulin Polymerization Promoting Protein Family Member 3 Suppresses Proliferation and Induces Apoptosis in Non-Small-Cell Lung Cancer

Abstract: Our previous studies demonstrated that depletion of tubulin polymerization promoting protein family member 3 (TPPP3) inhibits proliferation and induces apoptosis of HeLa cells. However, the expression and roles of TPPP3 in cancers remain largely unknown. In this study, we investigated the expression of TPPP3 in clinicopathological correlations in non-small-cell lung cancer (NSCLC) samples by immunohistochemistry. TPPP3 expression was significantly upregulated in NSCLC tissues, and high TPPP3 expression was pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 26 publications
4
30
2
Order By: Relevance
“…IHC staining was performed using a Ki-67 (Abcam, CA, USA) antibody according to the previous report [20]. …”
Section: Methodsmentioning
confidence: 99%
“…IHC staining was performed using a Ki-67 (Abcam, CA, USA) antibody according to the previous report [20]. …”
Section: Methodsmentioning
confidence: 99%
“…Ki67 is a nuclear protein that is closely linked to the proliferative potential of tumor. Recently, Ki67 was identified as an important prognostic factor for many tumor entities with respect to chemosensitivity and disease recurrence/death (Falato et al 2014;Li et al 2016;Rowe et al 2016). Its prognostic value in ovarian carcinoma remains controversial (Liu et al 2012;Masoumi-Moghaddam et al 2015;Feng et al 2016;Green et al 2016) and its correlation with VASH1 is not well known.…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of TPPP3 expression by RNA interference results in Lewis lung carcinoma (LLC) cell growth inhibition and cell cycle arrest demonstrating a lineage-specific dependency of lung cancer on TPPP3 [11]. Further investigation showed that inhibition of TPPP3 attenuated cell proliferation by inducing cell apoptosis and arresting cell cycle [10]. However, the potential role of TPPP3 in NSCLC development and metastasis remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously found that TPPP3 was significantly over-expressed in human NSCLC and associated with short overall survival [10]. Knockdown of TPPP3 expression by RNA interference results in Lewis lung carcinoma (LLC) cell growth inhibition and cell cycle arrest demonstrating a lineage-specific dependency of lung cancer on TPPP3 [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation